Monday

November 24, 2014

November 24, 2014

Posted by **Kyle** on Wednesday, October 30, 2013 at 10:40pm.

ln x + ln(x+1)=1

ln(x+5) = ln(x-1) - ln(x+1)

- Algebra -
**Steve**, Thursday, October 31, 2013 at 5:11amput to work the properties of logs.

ln x + ln(x+1) = 1

ln(x(x+1)) = 1

x(x+1) = e

x^2 + x - e = 0

then use the quadratic formula

ln(x+5) = ln(x-1)/ln(x+1)

ln(x+5) = ln((x-1)/(x+1))

x+5 = (x-1)/(x+1)

x^2+6x+5 = x-1

x^2+5x+6 = 0

...

**Answer this Question**

**Related Questions**

algebra 1 - I'm stuck on this problem. Can you help? -4x-9y=1 -x + 2y =-4 WHat ...

algebra - how would i find an equation of a line that goes through points(1,6) ...

Algebra - Translate each situation to a system of equations. Do not attempt to ...

College Algebra - Solve the system of equations with ROWOPS program. I know how ...

Algebra - Translate to a system of equations. DO NOT SOLVE. A nontoxic scouring ...

Math - How do I write the Symmetric Equation of a line given the following ...

Math - How do I write the Symmetric Equation of a line given the following ...

Algebra - Translate each problem into a system of equations. DO NOT attempt to ...

Algebra - I have been asked a question regarding inconsistency. How would I use ...

algebra - |5y-2| > 2 ok since it is greater than you would have to separate ...